2021
DOI: 10.1038/s41598-021-84591-1
|View full text |Cite
|
Sign up to set email alerts
|

The magnetic resonance imaging evaluation of condylar new bone remodeling after Yang’s TMJ arthroscopic surgery

Abstract: To evaluate the post-operative condylar bone remodeling after the treatment of Yang’s arthroscopic surgery. Consecutive cases from Jan 2017 to May 2018 that received Yang’s arthroscopic surgery were included in this study, the TMJ MRI examinations were performed preoperatively and postoperatively (follow up for 1 year or more), and condylar bone remodeling was estimated. A total of 229 patients (29 male and 200 female) were included in the study, 161 patients had new bone formation, and the average age was 17.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 24 publications
(9 reference statements)
1
11
0
Order By: Relevance
“…[26][27][28] However, the percentage of new bone formation after disk repositioning without ARS was decreased in older patients. 29 The current study confirmed the effect of condylar regeneration and mandibular growth after disk repositioning and ARS in young adults. The SNB angle increased and the ANB angle decreased.…”
Section: Discussionsupporting
confidence: 82%
“…[26][27][28] However, the percentage of new bone formation after disk repositioning without ARS was decreased in older patients. 29 The current study confirmed the effect of condylar regeneration and mandibular growth after disk repositioning and ARS in young adults. The SNB angle increased and the ANB angle decreased.…”
Section: Discussionsupporting
confidence: 82%
“…MRI scans were acquired by a 1.5-T imager (Signa, General Electric Medical Systems, Milwaukee, WI) with bilateral 3-inch TMJ surface coil receivers for all patients before and after operation and during follow-ups. Oblique sagittal images with closed- (proton density-weighted imaging, PDWI) and open-mouth (T2-weighted images, T2WI) positions and coronal images (T2WI) of the condyle were acquired for evaluation of disc position and condylar bone status [ 19 ]. When the posterior band of the disc was at the 1 to 2 o’clock position of the condyle, it was considered overcorrected and well positioned.…”
Section: Methodsmentioning
confidence: 99%
“…It presented as a rough and discontinuous cortical bone outline in the sagittal view with decreased condylar height as compared with baseline (Shen et al 2014; Liu et al 2018). At 6 mo after surgery, patients again underwent TMJ-MRI; according to which, new bone formation was defined as the condyle head presenting with a double cortical phenomenon and increased condylar height as compared with baseline (Liu et al 2018; Dong et al 2021)…”
Section: Methodsmentioning
confidence: 99%
“…Once severe resorption appears, complicated surgery is required, including arthroplasty and joint replacement, which might be physically and economically stressful for patients. Meanwhile, early intervention such as disc reposition is reported to promote condylar regeneration in some cases (Liu et al 2018; Dong et al 2021). This postoperative new bone, which is deemed a positive index of the treatment, can improve or even reverse facial deformity (Liu et al 2020).…”
Section: Introductionmentioning
confidence: 99%